Examining the perception of women's role in India's blue economy: A systematic literature review - Arakhita Behera (Asian Development Bank Institute (ADBI), 2024)
The primary objective of this paper is to conduct a systematic literature review on the perceptions and attitudes of women's employment and leadership in India's blue economy. The study uses a systematic literature review to look at studies and reports published from 1 January 2000 to 5 November 2022, to find out how people think and feel about women's participation with regard to employment and leadership in terms of taking decisions in traditionally male-dominated sectors i.e., fishing, marine shipping, and blue economy tourism. The evaluation closes with recommendations for the compilation of baseline inventories to collect gender-disaggregated data to advise policy on which sectors hinder women's participation as well as a new framework to create pathways for women's holistic participation in India's blue economy.
Keywords: J16; J81; Q22; Q26; J71; L83; N25; N75; P25; P46; Z32; F16; H11; 330; blue economy; women's employment; leadership; perceptions; attitudes; India